Direct PCR of fired shotgun casings: a South Australian evaluation. Issue 3 (4th May 2022) - Martin, Belinda; Plummer, Andrew; Linacre, Adrian; Henry, Julianne
ABSTRACT: Recovery of touch DNA from fired ammunition casings may provide vital forensic evidence for investigation and/or prosecution of firearm offences. Previous studies employing a direct PCR approach, where the traditional DNA extraction process is bypassed, have demonstrated an improved profiling success rate from some types of ammunition. To assess the potential value of these techniques to recover touch DNA from fired shotgun ammunition, direct PCR was evaluated for its ability to recover DNA profiles from fired 12 gauge Buckshot OOSG shotgun cartridges as compared to routine swabbing with DNA extraction. In this study, swabs subjected to direct PCR gave a significantly lower recovery of alleles than those undergoing DNA extraction. The presence of PCR inhibitors that were produced or deposited during the firing process may be the cause of these poorer results. The success of a direct PCR approach may therefore be directly related to the type of ammunition or firearm used and should therefore be specifically tested for individual case scenarios prior to employing it in forensic casework.